2006
DOI: 10.2353/ajpath.2006.060301
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Ubiquitin C-Terminal Hydrolase L1 in Mouse Ova and Its Function in the Plasma Membrane to Block Polyspermy

Abstract: Protein degradation is essential for oogenesis and embryogenesis. The ubiquitin-proteasome system regulates many cellular processes via the rapid degradation of specific proteins. Ubiquitin carboxylterminal hydrolase L1 (UCH-L1) is exclusively expressed in neurons , testis , ovary , and placenta , each of which has unique biological activities. However , the functional role of UCH-L1 in mouse oocytes remains unknown. Here , we report the expression pattern of UCH-L1 and its isozyme UCH-L3 in mouse ovaries and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 47 publications
8
59
0
1
Order By: Relevance
“…It has a subcortical location and is excluded from cell-cell contacts, as occurs with the SCMC. Decreased fecundity is observed in mice lacking UCHL1, which might be partly due to increased rates of polyspermy, the basis of which remains unknown (Table 1) (Sekiguchi et al, 2006). Whether or not these proteins directly participate in the SCMC remains to be determined.…”
Section: Protein-enriched Cell Cortexmentioning
confidence: 99%
“…It has a subcortical location and is excluded from cell-cell contacts, as occurs with the SCMC. Decreased fecundity is observed in mice lacking UCHL1, which might be partly due to increased rates of polyspermy, the basis of which remains unknown (Table 1) (Sekiguchi et al, 2006). Whether or not these proteins directly participate in the SCMC remains to be determined.…”
Section: Protein-enriched Cell Cortexmentioning
confidence: 99%
“…UCH-L1 is associated with the plasma membrane of oocytes (2) and with rat brain synaptic vesicles (26). To probe the potential basis for these observations, we studied the membrane-binding characteristics of UCH-L1 in synaptic vesicles isolated from rat brain.…”
Section: A Subpopulation Of Uch-l1 (Uch-l1 M ) Is Tightly Bound To Mementioning
confidence: 99%
“…acid protein whose expression is limited to few tissues, including brain, testes (1), ovaries (2), and certain peripheral tumors (3)(4)(5). UCH-L1 is robustly expressed in neurons, comprising 1-2% of total brain protein (6), and its absence in mice due to spontaneous intragenic deletions produces neurologic and neurodegenerative phenotypes (1,7).…”
mentioning
confidence: 99%
“…However, the role of UCHL1 in ova is largely unknown. We previously reported that UCHL1 is exclusively localized on the plasma membrane of mouse ova and plays an important role in the polyspermy block (Sekiguchi et al 2006). Polyspermic fertilization refers to the penetration of ova by two or more spermatozoa, resulting in the developmental failure of the zygote (Sun 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Susor et al (2010) showed that UCHL1 regulates CG reorganization and contributes to the ZP block using UCHL1 inhibitors. In contrast, 'gracile axonal dystrophy' (gad) female mice, which are autosomal recessive, spontaneous mutants carrying an intragenic deletion of the gene encoding UCHL1, show a significantly increased in vitro polyspermy rate and a decrease in litter size, even though gad mouse ova undergo a normal zona reaction (Saigoh et al 1999, Sekiguchi et al 2006. Thus, the role of UCHL1 in the mechanism of inhibiting polyspermy in mouse ova remains unclear.…”
Section: Introductionmentioning
confidence: 99%